Differing prevalence of microcephaly and macrocephaly in male and female fetuses - Brawley, Amalia M.; Schaefer, Eric W.; Lucarelli, Elizabeth; Ural, Serdar H.; Chuang, Cynthia H.; Hwang, Wenke; Paul, Ian M.; Daymont, Carrie (Frontiers in Global Women's Health, 2023)
Objective: To compare the proportion of female and male fetuses classified as microcephalic (head circumference [HC] <3rd percentile) and macrocephalic (>97th percentile) by commonly used sex-neutral growth curves. Methods: For fetuses evaluated at a single center, we retrospectively determined the percentile of the first fetal HC measurement between 16-0/7 and 21-6/7 weeks using the Hadlock, Intergrowth-21st, and NICHD growth curves. The association between sex and the likelihood of being classified as microcephalic or macrocephalic was evaluated with logistic regression. Results: Female fetuses (n=3,006) were more likely than male fetuses (n=3,186) to be classified as microcephalic using the Hadlock (0.4% male, 1.4% female; odds ratio female vs male 3.7, 95% CI [1.9, 7.0], p<0.001), Intergrowth-21st (0.5% male, 1.6% female; odds ratio female vs male 3.4, 95% CI [1.9, 6.1], p<0.001), and NICHD (0.3% male, 1.6% female; odds ratio female vs male 5.6, 95% CI [2.7, 11.5], p<0.001) curves. Male fetuses were more likely than female fetuses to be classified as macrocephalic using the Intergrowth-21st (6.0% male, 1.5% female; odds ratio male vs female 4.3, 95% CI [3.1, 6.0], p<0.001) and NICHD (4.7% male, 1.0% female; odds ratio male vs female 5.1, 95% CI [3.4, 7.6], p<0.001) curves. Very low proportions of fetuses were classified as macrocephalic using the Hadlock curves (0.2% male, <0.1% female; odds ratio male vs female 6.6, 95% CI [0.8, 52.6]). Conclusion: Female fetuses were more likely to be classified as microcephalic, and male fetuses were more likely to be classified as macrocephalic. Sex-specific fetal head circumference growth curves could improve interpretation of fetal head circumference measurements, potentially decreasing over- and under-diagnosis of microcephaly and macrocephaly based on sex, therefore improving guidance for clinical decisions. Additionally, the overall prevalence of atypical head size varied using three growth curves, with the NICHD and Intergrowth-21st curves fitting our population better than the Hadlock curves. The choice of fetal head circumference growth curves may substantially impact clinical care.